Vivienda Sostenible Para El Envejecimiento Activo (2022)
Older adults face two important global challenges that have to do with the deterioration of health due to the effects of aging and exclusion by the state, the lack of opportunities and their relatives, to this we must include the development of housing that it forms the city that is built and conceived spontaneously and empirically, in addition to the other case of planned collective housing from the impact and new needs that arise from the industrial revolution, the modern movement and hygiene; They are housing proposals and processes that failed to foresee in the design the changes that people experience over time, therefore they have had to adapt the home according to their needs, but they did not manage to change the environment.